Representações do feminino no cinema e na memória da resistência armada à ditadura militar brasileira - Carolina Dellamore; Juliana Ventura de Souza Fernandes (L'Ordinaire des Amériques)
The article aims to analyze the documentary Em busca de Iara (2014), directed by Flávio Frederico. The film aims to reconstruct the trajectory of political activist Iara Iavelberg, whose narrative is led by Mariana Pamplona, niece of Iara and responsible for the script, production and co-direction of this work. However, the focus of the documentary is the dismantling of the official version of the dictatorship, which attributed suicide to Iara’s death in 1971. Thus, in the investigative urge to prove that Iara Iavelberg was murdered by repression, the documentary relegates a secondary plan his political militancy during the dictatorship. The central argument is that in the documentary the guerrilla Iara remains recognized for her beauty and for being the lover of former army captain Carlos Lamarca and not for her political activities, which contributes little to the discussion of the role of women militancy in organizations the left.